2020
DOI: 10.3390/foods9091322
|View full text |Cite
|
Sign up to set email alerts
|

Technological Feature Assessment of Lactic Acid Bacteria Isolated from Cricket Powder’s Spontaneous Fermentation as Potential Starters for Cricket-Wheat Bread Production

Abstract: The bacterial community profile of cricket powder highlighted the presence of four main genera: Bacteroides spp., Parabacteroides spp., Lactococcus spp., and Enterococcus spp. The spontaneous fermentation of cricket powder allowed for the isolation and characterization of seven lactic acid bacteria strains belonging to six species: Latilactobacillus curvatus, Lactiplantibacillus plantarum, Latilactobacillus sakei, Lactococcus garvieae, Weissella confusa, and Enterococcus durans. The strains were characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 59 publications
(73 reference statements)
1
25
0
Order By: Relevance
“…Interestingly, cakes are essential for celebrating various types of occasions, favored for children, serving consumers with wide age-grouping, used as a snack between diets, or as desserts post meals during dine-out. However, to help customers fulfill their nutritional requirements, food fortification is a helpful and valuable technique [ 38 , 39 , 40 , 59 ]. Fortification is not materializing as one single issue to that purpose, but also coexists for dietary diversification and supplementation approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, cakes are essential for celebrating various types of occasions, favored for children, serving consumers with wide age-grouping, used as a snack between diets, or as desserts post meals during dine-out. However, to help customers fulfill their nutritional requirements, food fortification is a helpful and valuable technique [ 38 , 39 , 40 , 59 ]. Fortification is not materializing as one single issue to that purpose, but also coexists for dietary diversification and supplementation approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention needs to be paid to the milling process (both for wheat and for BPF) [ 37 ], dough rheology [ 4 , 5 ], and final cake characteristics [ 4 , 5 ]. Moreover, to the best of the authors’ knowledge, the literature review mainly highlighted the substitution of WF with interesting alternative flours like insects [ 38 , 39 ], legumes [ 40 ], and other by-products [ 41 ], but only a few studies considered substitutions with BPF flours, which need further investigation, thus motivating this work. Therefore, this study aimed to investigate the effects of WF substitution with 5%, 10%, and 15% of BPF on the chemical composition, minerals, and amino acids content, total phenolic content (TPC), and antioxidant activity (AOA); rheological parameters of different substituted flour and sensory evaluation of baked cakes were performed as well.…”
Section: Introductionmentioning
confidence: 99%
“…This has increased significantly the research efforts for alternative, cheaper, and more sustainable sources of protein. In this context, insects and legumes seem to be the best opportunities in breadmaking [48][49][50][51][52][53][54][55][56].…”
Section: Use Of Alternative Sources Of Protein In Breadmakingmentioning
confidence: 99%
“…In relation to the use of chickpea in breadmaking, the literature review did not highlight only positive effects on the environment. Galli et al (2020) [51] highlighted the interesting capacity of indigenous Weissella confusa, isolated from chickpea sourdough, to produce, in situ, bacterial exopolysaccharides. Moreover, [50] found that the substitution with 5% of chickpea flour proved to be an excellent technological improver for ancient wheat flour.…”
Section: Use Of Alternative Sources Of Protein In Breadmakingmentioning
confidence: 99%
“…The use of lactic acid bacteria (LAB) in the agri-food industry has evolved exponentially over the years as they possess technological properties that can be exploited at the industrial level. These include proteolytic, cellulolytic, flavoring, amylolytic, texturizing, but also their ability to produce lactic acid ( Elmaged et al., 2015 ; Herdian et al., 2018 ; Galli et al., 2020 ). Indeed, lactic acid (LA) is an organic compound that plays a role in multiple biochemical processes; it has various applications cosmetic, pharmaceutical, chemical and food industries ( Mohan et al., 2015 ; Battula et al., 2018 ; Abedi and Hashemi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%